Evaluating the implementation of a longitudinal cocurricular experiential quality improvement training programme for undergraduate medical students - Alison Freeland; Katherine Bailey; Farah Khan; Nazia Sharfuddin; Ke Xin Lin; Elina Farahani; Sunny Raval; Muhammadhasan Nasser; Jonathan Hersh; Shaan Chugh; Amir Ginzburg (BMJ Open Quality)
Quality improvement and patient safety (QIPS) is a core competency in undergraduate medical education. While didactic and experiential learning enhance QIPS knowledge and skills, there are limited experiential opportunities. This study aims to evaluate the feasibility and effectiveness of a longitudinal didactic and experiential student-led programme, Quality Improvement Experiential Student Training (QuEST). QuEST was piloted during year 1, where learners completed online modules, didactic seminars, an experiential project and mentorship meetings with the programme’s faculty chair (Plan-Do-Study-Act [PDSA] 1). We implemented a formal leadership structure, adapted the curriculum, and changed mentorship meetings to student-led in year 2 (PDSA 2). In response to reduced learner satisfaction, we reintroduced faculty-led mentorship meetings in year 3 as well as revised the experiential project screening process and decreased the cohort size to enhance programme operations. The outcome was self-reported confidence in completing a QIPS project, which we aimed to achieve at least 60% of learners reporting confidence each year. Fourteen learners were enrolled in year 1, 45 in year 2 and 18 in year 3. After year 1, 86% of learners reported confidence in completing a QIPS project (from 39% preprogramme; p<0.01), 64% in year 2 (from 16%; p<0.01) and 75% in year 3 (from 28%; p<0.01). Programme satisfaction was 4.25/5 in year 1, 4.27/5 in year 2 and 4.75/5 in year 3. Strengths included experiential learning and support from the programme. Opportunities for improvement included further check-in meetings to promote accountability and project progression. The QuEST programme equipped learners with the confidence needed to complete a QIPS project. The provision of mentorship was identified as a common driver for learner satisfaction, with the suggestion to provide further structured and unstructured mentorship opportunities embedded in the programme. Future work may consider longitudinally assessing changes to learner behaviour.